2004
DOI: 10.1016/s1078-5884(03)00601-4
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Varicose Veins: Incidence, Risk Factors and Groin Anatomy

Abstract: Objectives. To investigate the recurrence rate after sapheno-femoral junction (SFJ) ligation and great saphenous vein (GSV) stripping for varicose veins (VV), to evaluate risk factors for recurrence and to classify the anatomy of the recurrence in the groin. Design. Clinical follow-up study. Methods. Eighty-nine consecutive patients with 100 operated legs were reexamined clinically and with duplex after 6-10 years. Fourteen groins were re-explored, 13 after varicography. The anatomy in the groin was classified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
0
7
1
Order By: Relevance
“…217 In a multicenter registry that included 199 limbs of 170 patients with REVAS, the most frequent sources of recurrent reflux were the SFJ (47.2%), followed by leg perforators (54.7%), neovascularization (20%), and technical failure (19%); both neovascularization and technical failure occurred in 17%, and in 35%, the cause was uncertain or unknown. 215 In a study of 279 limbs with recurrent varicose veins at the groin, Geier et al 223 found a long residual saphenofemoral stump in about two-thirds of cases, recurrences became apparent after a mean time interval of 6.3 years, and symptoms occurred after a mean of 8.5 years.…”
Section: Results Of Open Venous Surgerymentioning
confidence: 98%
See 1 more Smart Citation
“…217 In a multicenter registry that included 199 limbs of 170 patients with REVAS, the most frequent sources of recurrent reflux were the SFJ (47.2%), followed by leg perforators (54.7%), neovascularization (20%), and technical failure (19%); both neovascularization and technical failure occurred in 17%, and in 35%, the cause was uncertain or unknown. 215 In a study of 279 limbs with recurrent varicose veins at the groin, Geier et al 223 found a long residual saphenofemoral stump in about two-thirds of cases, recurrences became apparent after a mean time interval of 6.3 years, and symptoms occurred after a mean of 8.5 years.…”
Section: Results Of Open Venous Surgerymentioning
confidence: 98%
“…Recurrent varicose veins after surgery (REVAS) have been reported at rates ranging from 6.6% to 37% at 2 years 177,215,216 and up to 51% at 5 years. [217][218][219][220][221][222] Most studies reported 2-year clinical recurrence rates of 20% to 37% after conventional or cryostripping, when residual or recurrent varicose veins noted by both the patient and the surgeon were counted.…”
Section: Results Of Open Venous Surgerymentioning
confidence: 99%
“…3 We introduced EVLA rather tentatively at St Franziskus Hospital in 2002 and continued to dissect the SFJ, because correct SFJ dissection was deemed mandatory before the introduction of endovenous treatment to avoid high rates of groin recurrence. 4 Long-term data about groin recurrence after minimally invasive GSV treatment without SFJ dissection are not yet available.…”
mentioning
confidence: 99%
“…The main disadvantages of varicose vein surgery are postoperative pains and discomfort, bruising and hyperpigmentation, lymphoceles and hematomas (mainly in obese patients and in the case of redo surgery in the groin), inesthetic scars, and a 20% to 60% rate of incidence of recurrent varicose veins [31,32]. Usually, inappropriate or incomplete ligation at the saphenofemoral/popliteal junction level, or more generally an inappropriate or incorrect original operation, an incorrect assessment of the varicose vein network, and lack of phlebologic follow-up are generally thought to be the main causes of recurrent varicose veins.…”
Section: Surgerymentioning
confidence: 99%